When breath becomes air - Kalanithi, Paul; Verghese, Abraham, 1955 (London: Vintage, 2018)
"At the age of 36, on the verge of a completing a decade's worth of training as a neurosurgeon, Paul Kalanithi's health began to falter. He started losing weight and was wracked by waves of excruciating back pain. A CT scan confirmed what Paul, deep down, had suspected: he had stage four lung cancer, widely disseminated. One day, he was a doctor making a living treating the dying, and the next, he was a patient struggling to live. Just like that, the future he and his wife had imagined, the culmination of decades of striving, evaporated. With incredible literary quality, philosophical acuity, and medical authority, When Breath Becomes Air approaches the questions raised by facing mortality from the dual perspective of the neurosurgeon who spent a decade meeting patients in the twilight between life and death, and the terminally ill patient who suddenly found himself living in that liminality. At the base of Paul's inquiry are essential questions, such as: What makes life worth living in the face of death? What happens when the future, instead of being a ladder toward the goals of life, flattens out into a perpetual present? When faced with a terminal diagnosis, what does it mean to have a child, to nuture a new life as another one fades away? As Paul wrote, "Before my cancer was diagnosed, I knew that someday I would die, but I didn't know when. After the diagnosis, I knew that someday I would die, but I didn't know when. But now I knew it acutely. The problem wasn't really a scientific one. The fact of death is unsettling. Yet there is no other way to live." Paul Kalanithi passed away in March 2015, while working on this book"--
In English
Keywords: Kalanithi, Paul -- Health; Lungs -- Biography. -- Cancer -- Patients -- United States; Neurosurgeons -- Biography; Husband and wife; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs